Preparation of foamed and unfoamed geopolymer/NaX zeolite/activated carbon composites for CO2 adsorption. (1st January 2022) - Candamano, S.; Policicchio, A.; Conte, G.; Abarca, R.; Algieri, C.; Chakraborty, S.; Curcio, S.; Calabrò, V.; Crea, F.; Agostino, R.G.
Abstract: The article reports the preparation of novel composites with hierarchical porosity and their evaluation as CO2 adsorbents. An activator solution and metakaolin were used as starting mix. Activated carbon, characterized by a surface area of 528 m 2 /g and a bimodal porosity centered at 4.2 Å and 10 Å, was added to the starting mix to produce hybrid composites. It was in-house produced by thermo-chemical activation of olive pomace waste. H2 O2 and egg protein were added to the mix as a facile method to produce foamed composites. Multiphase reaction–crystallization processes, characterized by one or two thermal steps, were designed to favor geopolymerization and in-situ NaX zeolite gel conversion of metakaolin. Both the thermal procedures produce composites in forms of monoliths, as needed for application in real processes. The two thermal steps process, of which the latter is hydrothermal, increases the amount of NaX crystalline phase produced. The foaming process decreases the density and the mechanical properties of the monoliths but it does not affect the geopolymerization and crystallization reactions or the topology of the produced zeolite. The combination of raw materials and thermal treatments affect the textural properties of the adsorbents, mainly in terms of different contribution of ultramicroporosity (<7 Å) and super microporosity (7–20 Å). Several CO2 adsorption/desorption measurements at room temperature (298 K) up to 15 bar were carried out on all the prepared adsorbents. The information about the textural properties was promptly used to explain the different CO2 storage capacities, the different behaviours in the reversibility of the single adsorption/desorption process and the different decrease of the maximum storage capacity of the composites with cycling. Notably, all the adsorbents store, already at 1 bar, almost 60% of the CO2 uptake at the maximum analyzed pressure. The strength of solid-gas interaction was also assessed by the calculating the values of Toth equation fitting parameter K. The proposed robust and facile preparation processes are aimed to obtain adsorbents able to overcome the shortcomings of conventional packed beds by exploiting the binding properties of geopolymer, the adsorption properties of zeolite NaX, the tailored pore structure, the electrical conductibility and the high stability of activated biochar and the macroporosity introduced by the foaming agent. Graphical abstract: Image 1 Highlights: Olive pomace was used to produce activated carbon with mixed pore size distribution. Monoliths were obtained via geopolymerization followed by in situ NaX gel conversion. H2 O2, egg protein and activated carbon were used to produce foamed/hybrid monoliths. High CO2 capacity was measured in foamed/unfoamed multiphase hybrid monoliths. High adsorbent/CO2 strength of interaction was found using Toth/Langmuir model.